Evaluación presupuestaria al gobierno autónomo descentralizado municipal Centinela del Cóndor, provincia de Zamora Chinchipe, período 2018-2019 - Jaramillo Romero, Marilyn Vicenta (2021)
The present thesis called "BUDGET EVALUATION OF THE AUTONOMOUS DECENTRALIZED MUNICIPAL GOVERNMENT CENTINELA DEL CÓNDOR, PROVINCE OF ZAMORA CHINCHIPE, PERIOD 2018 - 2019" was executed in compliance with the prerequisite to opt for the Title and title of Public Engineering in Accounting and Auditing, Accountant. The methodology for the development of this thesis work initially consisted of the theoretical study about the research topic and then the complementary part for the development of the practice began with the collection of information such as: annual operating plan, state of execution budget, initial budget and the budget schedules of income and expenses of the entity for periods 2018 and 2019, to obtain a better perception of the behavior of each of the budget items. To measure the efficiency and effectiveness in the development of the activities, the budgetary financial indicators and a comparative analysis of the variations of the budget items were applied, which for a better understanding were graphically represented and interpreted. As a result of the thesis work and from the general point of view, it was determined that the income has not been estimated correctly since the accrued income for the 2018 period is $ 5,560,493.42, compared to the Coded Income that is $ 6,396 .211.30 giving a difference of $ 835,717.88. In 2019, the accrued income is $ 5,962,847.65 and they were Coded to be $ 7,186,227.48 giving a difference of $ 1,223,379.83, these indicate that there was bad planning since these resources where They were able to invest in works for the benefit of the inhabitants of the canton. At the end of the thesis work, a report was prepared for the mayor of the Decentralized Autonomous Government of the Centinela del Cóndor Canton, which was carried out based on the results obtained in the preparation of the evaluation, which allows the correct taking decision-making by the administrators of the institution. In general, it was established that the Decentralized Autonomous Government of the Centinela del Cóndor Canton has not carried out a budget evaluation in a correct and timely manner in the analyzed period, making it impossible to detect shortcomings such as the lack of initial allocation of resources to comply with the programs. established in the annual operating plan, since it was concluded that of the projects programmed for the 2018 period, 48.76% were completed and for 2019 they were 35.43%, which undoubtedly reflects a deficiency in their execution and due to they constantly carry out budgetary reforms causing a low level of efficiency and effectiveness; Therefore, it is recommended to carry out budget evaluations at the end of the fiscal period as established by the Ministry of Economy and Finance and in this way implement the necessary corrective measures. Keywords: Evaluation, Budget, Budget Cycle, Annual Operating Plan, Budget Execution Status, Income, Expenses